Trend of exercise before, During, and after Pregnancy - Sara Esmaelzadeh saeyeh; Simin Taavoni; Zahra Ahmadi; Hamid Haghani (Iran University of Medical Sciences, 2008)
Background and Aim: Pregnancy and Postpartum is the best period for gaining health behaviors, including exercise, to promote quality of life is pregnancy and postpartum. The aim of the present study was to examine the trend of exercise activities before, During and after pregnancy.   Material and method: This was a retrospective longitudinal study, in which 225 women were enrolled by continuous sampling.   Result: The most frequent exercise, before, during and after pregnancy was walking. The result of Repeated measure test showed that trend of exercise before pregnancy to 3 months after that was negative.   Conclusion: This study showed that the trend of physical activity decreased from the priod before pregnancy to 3 month after that, so it is suggested that professional care in prenatal ward, vaccination clinic and family planning clinic focus on encouraging women to continue their activity, during and after pregnancy.